New Challenges for the Design of High Value Plant Products: Stabilization of Anthocyanins in Plant Vacuoles - Passeri, Valentina; Koes, Ronald; Quattrocchio, Francesca M. (Frontiers in Plant Science, 2016)
In the last decade plant biotechnologists and breeders have made several attempt to improve the antioxidant content of plant-derived food. Most efforts concentrated on increasing the synthesis of antioxidants, in particular anthocyanins, by inducing the transcription of genes encoding the synthesizing enzymes. We present here an overview of economically interesting plant species, both food crops and ornamentals, in which anthocyanin content was improved by traditional breeding or transgenesis. Old genetic studies in petunia and more recent biochemical work in brunfelsia, have shown that after synthesis and compartmentalization in the vacuole, anthocyanins need to be stabilized to preserve the color of the plant tissue over time. The final yield of antioxidant molecules is the result of the balance between synthesis and degradation. Therefore the understanding of the mechanism that determine molecule stabilization in the vacuolar lumen is the next step that needs to be taken to further improve the anthocyanin content in food. In several species a phenomenon known as fading is responsible for the disappearance of pigmentation which in some case can be nearly complete. We discuss the present knowledge about the genetic and biochemical factors involved in pigment preservation/destabilization in plant cells. The improvement of our understanding of the fading process will supply new tools for both biotechnological approaches and marker-assisted breeding.